Principles and practice of clinical research - Gallin, John I.; Ognibene, Frederick P. (Academic Press, 2017)
Principles and Practice of Clinical Research, Fourth Edition has been thoroughly revised to provide a comprehensive look at both the fundamental principles and expanding practice of clinical research. New to this edition of this highly regarded reference, authors have focused on examples that broadly reflect clinical research on a global scale while including a discussion of international regulations, studies, and implications. In addition to key topics such as bioethics, clinical outcome data, cultural diversity, protocol guidelines, and "omic platforms, this edition contains new chapters devoted to electronic health records and informational resources for clinical researchers, as well as the many opportunities associated with big data. Covering a vast number of topics and practical advice for both novice and advanced clinical investigators, this book is a highly relevant and essential resource for all those involved in conducting human research.